Design Thinking David Kelley & Tim Brown: Otak Dibalik Penciptaan Aplikasi Gojek - Muhammad Lutfi Lazuardi; Iwan Sukoco (Universitas Winaya Mukti, 2019)
This study aims to describe each stage of design thinking at PT Karya Anak Bangsa (Gojek) to create appropriate and practical solutions to problems that arise in the community. The methodology used for this research was a literature review with descriptive analysis and identification with David Kelley & Tim Brown's theory. The expert opinion of each explanation strengthens it. The results of this study were that with a good design thinking process PT Aplikasi Karya Anak Bangsa (Gojek) had produced a variety of solutions that were only online-based transportation applications. However, currently, Gojek also created a variety of services according to various community needs. It was also able to create business opportunities from a problem that occurred in the community.